Groundwater in Southwestern Algeria: An Essential Heritage and Keys to Development - MERZOUGUI Touhami; Cherif Rezzoug; et Remini Boualem (Journal of Water, 2023)
A regional overview describes groundwater resources in Southwestern Algeria, assessing challenges and strategies for sustainable development under climatic and demand pressures.
Keywords: UroscopyGroundwater